Harnessing the small intestinal axis to resolve systemic inflammation - Bodmer, Mark; Itano, Andrea; McInnes, Iain (Frontiers in Immunology, 2022)
This Perspective presents the potential of the Small Intestinal Axis, a sub-division of the Gut-immune Axis, to modulate systemic inflammation based on sensing contents of the gut lumen. Gut mucosal immunity regulates tolerance to food and gut contents and is also a significant factor in maintaining systemic homeostasis without compromising immunity to pathogens. This is achieved through anatomical structures and signaling pathways that link the tolerogenic potential of the proximal small intestine to systemic immunity. Non-live microbes isolated from human small intestinal mucosa, and the extracellular vesicles (EVs) which they shed, can resolve systemic inflammation without systemic exposure after oral delivery. The mechanism involves primary interactions with pattern recognition receptors followed by trafficking of immune cells through mesenteric lymph nodes. This generates in the periphery a population of circulating CD4+ T-cells which have regulatory function but an atypical FoxP3- phenotype. There is no parallel modification of the resident gut microbiome. Discoveries using this novel approach of targeting mucosal microbial elements to the tolerogenic proximal regions of the small intestine are revealing some of the mysteries of the relationship between the gut and immune system. This is, in turn, opening a potential new field of effective and safe medicines for inflammatory diseases.